Kinematic instep kicking differences between elite female and male soccer players - Barfield, W. R.; Kirkendall, D. T.; Yu, B. (Journal of Sports Science & Medicine, 2002)
The rapid rise in female participation in soccer worldwide has not been followed by a corresponding increase in the number of studies biomechanically that target female kicking patterns to determine if differences exist between males and females. The objectives of this study were to examine kinematic instep kicking differences between elite female and male soccer players in dominant and nondominant limbs. Eight elite soccer players, six females and two males, volunteered as subjects in the study. Subjects took a two-step angled approach of 45-60 degrees to a stationary soccer ball positioned between two force platforms and kicked the ball with the instep portion of the foot as hard as possible into netting which was draped from the ceiling. Ball velocity was the dependent variable. We evaluated six additional variables that have previously been shown to be important predictors of instep kicking ball speed. The males generally kicked the ball faster than the females and displayed greater kinematic variables, including maximum toe velocity, ball contact ball velocity, mean toe velocity, mean toe acceleration, and ankle velocity at ball contact, all of which contributed to faster ball speed. There was one exception. One of the elite females kicked faster than the two elite males and demonstrated higher or similar kinematic patterns when compared with the males. Our conclusions were that females do not instep kick the ball as fast as males, but there are exceptions as our data demonstrates.